A Discourse Analysis of Dikili Tradition in Modikili Practice for Preserving Gorontalo Cultural Language Representation - Sri Harkeni Mohune; Harto S. Malik; Rahman Taufiqrianto Dako (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze how language in the Dikili tradition, performed through Modikili practices, represents and preserves Gorontalo culture. A qualitative descriptive approach was used to obtain a deeper understanding of the ritual language found in the tradition. The study applied Norman Fairclough’s Critical Discourse Analysis, focusing on textual, discursive, and social dimensions. Data were collected through participant observation, documentation of ritual utterances, and semi-structured interviews with cultural practitioners and community members. The data were analyzed using thematic analysis to identify patterns of meaning and cultural representation within the discourse. The findings show that the Dikili tradition contains religious metaphors, repetition, parallel structures, and poetic expressions that reflect spiritual values, social harmony, and collective identity. In addition, Modikili practices serve as a medium for preserving and passing down local wisdom across generations. In conclusion, the ritual language used in the Dikili tradition is not only a symbolic expression but also an important cultural practice that helps maintain Gorontalo cultural identity in modern society.